2020
DOI: 10.1002/ajmg.a.62002
|View full text |Cite
|
Sign up to set email alerts
|

Returning negative results from large‐scale genomic screening: Experiences from the eMERGE III network

Abstract: Population‐based genomic screening has the potential to improve health outcomes by identifying genetic causes of disease before they occur. While much attention has been paid to supporting the needs of the small percentage of patients who will receive a life‐altering positive genomic screening result that requires medical attention, little attention has been given to the communication of negative screening results. As there are currently no best practices for returning negative genomic screening results, we dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Our data suggest that these features of the research environment may introduce specific challenges to the return of results process. Our findings support the conclusion that these aspects of research sequencing may need to be described in plain language materials to accompany uninformative test reports that often include technical jargon (Finn et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our data suggest that these features of the research environment may introduce specific challenges to the return of results process. Our findings support the conclusion that these aspects of research sequencing may need to be described in plain language materials to accompany uninformative test reports that often include technical jargon (Finn et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…One prior multi-site study found that the most common approach is to return uninformative results to patients via postal mail or secure email without genetic counseling by default. Differences in procedures for returning these results included: variations in terminology used to describe "negative" or uninformative results, differing guidance regarding the meaning of these results for participants and their family members, and varied recommendations for clinical follow-up (Finn et al, 2021). Recent surveys conducted in patients with colon polyps or hypercholesterolemia suggested that when uninformative results are returned to patients by mail without counseling, roughly one-third of patients will erroneously infer a lowered risk of disease based on this information, with almost twice as many women as men lowering their perception of disease risk (Stuttgen, Pacyna, Beck, et al, 2020).…”
mentioning
confidence: 99%
“… 58 In addition, one site returned variants of uncertain significance (VUSs) for one disorder. Negative results were returned to participants at some sites, 64 , 65 , 66 and one site returned carrier status. 35 Sites also varied in whether they re-interpreted results over time in light of new information about clinical significance.…”
Section: Returning Results To Participants and Their Health Care Prov...mentioning
confidence: 99%
“…There was much greater variation across sites in how negative results were returned. 24 , 66 While recipients who were informed that they did not have actionable results were generally content with the process, 77 some of the respondents incorrectly felt that they had less or no residual risk. 74 , 77 …”
Section: Returning Results To Participants and Their Health Care Prov...mentioning
confidence: 99%
“…For example, 1 site disclosed heterozygous status for common autosomal recessive conditions, 4 sites disclosed pharmacogenomic information, and 6 sites disclosed null result information. 12 Variants of uncertain significance were disclosed for colorectal cancer at the KPWA/UW site in conjunction with enhanced recruitment at that site for participants with colorectal cancer and colon polyps. Sequencing laboratories began releasing results to clinical sites in November 2017, and for the purposes of this report, were considered complete as of April 2020 (see eMERGE Clinical Annotation Working Group 13 for details on distribution of returned findings).…”
Section: Emerge3 Sequencingmentioning
confidence: 99%